2022
DOI: 10.1002/2211-5463.13359
|View full text |Cite
|
Sign up to set email alerts
|

VDAC1 oligomerization may enhance DDP‐induced hepatocyte apoptosis by exacerbating oxidative stress and mitochondrial DNA damage

Abstract: Cisplatin (DDP)‐based chemotherapy is a preferred treatment for a broad spectrum of cancers, but the precise mechanisms of its hepatotoxicity are not yet clear. Recently, the role of voltage‐dependent anion channel protein 1 (VDAC1) in mitochondrial activity and cell apoptosis has attracted much attention. Our aim was to investigate the effects of mitochondrial outer membrane protein VDAC1 oligomerization in DDP‐induced hepatocyte apoptosis. L‐02 hepatocytes were divided into 4 groups: (a) control group, (b) 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The mechanisms of cisplatin-induced hepatorenal toxicity are related to mitochondrial dysfunction, oxidative stress, and inflammation [ 4 , 5 ]. Therefore, we evaluated the roles of SVPr1 and SVPr2 in improving mitochondrial dysfunction, oxidative stress, and inflammation in the liver and kidney induced by cisplatin.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanisms of cisplatin-induced hepatorenal toxicity are related to mitochondrial dysfunction, oxidative stress, and inflammation [ 4 , 5 ]. Therefore, we evaluated the roles of SVPr1 and SVPr2 in improving mitochondrial dysfunction, oxidative stress, and inflammation in the liver and kidney induced by cisplatin.…”
Section: Resultsmentioning
confidence: 99%
“…Cisplatin induces an imbalance in the levels of oxidative stress and inflammatory response in the liver and kidney [ 4 , 5 ], whereas SVPr1 and SVPr2 administration could reduce cisplatin-induced adverse reactions by modulating the gut microbiota and metabolic pathways. To explore the possibility that the mitigation of cisplatin-induced injury by sika deer antler protein treatment may be initiated by pathogenic microbes and establish correlations between the presence of certain bacteria with the relief of hepatic and renal toxicity in mice, we performed microbiome analysis based on 16S rRNA sequencing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C4 exhibited elevated expression levels of Kif26b, Itgbl1, Nox4, Pcdh9, and Xkr4. C5 showed elevated expression levels of mitochondrial transcripts, such as mt-Atp6, mt-Cytb, mt-Co3, and mt-Nd2, indicating a notable mitochondrial malfunction that could trigger CM apoptosis during this stage [25][26][27][28] (Fig. 2c).…”
Section: Snrna-seq Revealed the Heterogeneity And Subclusters Of MI Cmsmentioning
confidence: 99%
“…Similarly, cytoplasmic translocation of mtDNA has been detected in many disease states and has been associated with cancer progression ( Liu et al, 2019b ; Piantadosi, 2020 ). In particular, when tumor cells are often subjected to multiple physicochemical insults during treatment, their mitochondrial damage is further aggravated and more mtDNA is released into the cytoplasm ( Cheng et al, 2020 ; Zhu et al, 2022 ). Numerous studies have shown that mtDNA is a potent inducer of cGAS-STING signaling ( Wu et al, 2021b ).…”
Section: Mtdna Is a Potent Inducer Of The Cgas-sting Pathwaymentioning
confidence: 99%